(untitled) (International Journal of Innovative Research in Engineering & Management, 2024)
This paper presents a GPS tracking system for an ultrasonic blind stick. People with visual impairments have historically used sticks to detect obstructions in their path. But the person using this stick has to deal with a number of issues because it is inefficient in a number of ways. Giving visually challenged people a better navigational aid is the aim of this initiative. Thanks to the use of sensors, object recognition is made easier with the ultrasonic blind walking stick than with the regular walking stick. The data on his present location is provided by his GPS system.In the event that the blind person loses track of where they put their stick, the system has an additional sophisticated tool to assist them. Blind Stick the ultrasonic blind stick with GPS tracking device is described in the paper’s abstract. Historically, those who are blind or visually challenged have utilized a stick to detect obstructions in their path. However, there are a number of inefficiencies with this stick, and the user must deal with a number of issues. Better navigational aids for the blind and visually handicapped are the aim of this study. Because it uses sensors to facilitate object identification, the ultrasonic blind walking stick is far more sophisticated than the conventional walking stick. Information about his present location is provided by his GPS system. One other cutting-edge feature built into the system will assist blind people in finding their stick in the event that they misplace it.